Identification of a novel perifornical-hypothalamic-area-projecting serotonergic system that inhibits innate panic and conditioned fear responses - Cristian S. Bernabe; Izabela F. Caliman; Aline R. R. de Abreu; Andrei I. Molosh; William A. Truitt; Anantha Shekhar; Philip L. Johnson (Translational Psychiatry, 2024)
Abstract The serotonin (5-HT) system is heavily implicated in the regulation of anxiety and trauma-related disorders such as panic disorder and post-traumatic stress disorder, respectively. However, the neural mechanisms of how serotonergic neurotransmission regulates innate panic and fear brain networks are poorly understood. Our earlier studies have identified that orexin (OX)/glutamate neurons within the perifornical hypothalamic area (PFA) play a critical role in adaptive and pathological panic and fear. While site-specific and electrophysiological studies have shown that intracranial injection and bath application of 5-HT inhibits PFA neurons via 5-HT1a receptors, they largely ignore circuit-specific neurotransmission and its physiological properties that occur in vivo. Here, we investigate the role of raphe nuclei 5-HT inputs into the PFA in panic and fear behaviors. We initially confirmed that photostimulation of glutamatergic neurons in the PFA of rats produces robust cardioexcitation and flight/aversive behaviors resembling panic-like responses. Using the retrograde tracer cholera toxin B, we determined that the PFA receives discrete innervation of serotonergic neurons clustered in the lateral wings of the dorsal (lwDRN) and in the median (MRN) raphe nuclei. Selective lesions of these serotonergic projections with saporin toxin resulted in similar panic-like responses during the suffocation-related CO2 challenge and increased freezing to fear-conditioning paradigm. Conversely, selective stimulation of serotonergic fibers in the PFA attenuated both flight/escape behaviors and cardioexcitation responses elicited by the CO2 challenge and induced conditioned place preference. The data here support the hypothesis that PFA projecting 5-HT neurons in the lwDRN/MRN represents a panic/fear-off circuit and may also play a role in reward behavior.